Archaische Siedlungsbefunde in Ephesos, Katalog- und Tafelband Stratigraphie, Bauphasen, Keramik und Kleinfunde aus den Grabungen unter der Tetragonos-Agora. Archaische Keramikfunde aus dem Theater und von den nordwestlichen Ausläufern des Panayırdağ - von Miller, Alexandra Ch. J. (Verlag der Österreichischen Akademie der Wissenschaften, 2019)
The study deals in a holistic manner with the archaic settlement residuals (stratigraphy, architectural remains, pottery and small finds) from excavations underneath the Tetragonos-Agora at Ephesos. The findings from other two find spots are included in order to better discuss typo-chronological and functional questions.